A numerical investigation on hydrodynamic interaction coefficients for two freely floating barges of tandem configuration in waves - Ali, Mir Tareque; Sobahani, G (Journal of Naval Architecture and Marine Engineering, 2023)
While installing offshore structures two or more structures are observed floating close to each other in waves. Consequently, the adjacent floating structures influence the fluid loading on each body. Due to radiated waves produced by the motion of adjoining floating structures and the wave reflection or, sheltering effect because of the presence of these nearby structures, the wave loading for the multi-body case will be quite different from that of a single-body case. Accurate computation of hydrodynamic interaction coefficients and hydrodynamic coefficients are vital for a multiple floating body case since the motion response prediction uses these parameters in solving the 6xN simultaneous equations (where N is the number of closely floating structures). The hydrodynamic interaction coefficients are investigated in this paper for two three-dimensional (3-D) structures floating closely in water. A commercial hydrodynamic software named Hydrostar (introduced by Bureau Veritas) which is based on linear three-dimensional potential theory is adopted for numerical simulations of the present problem. To validate the numerical results for hydrodynamic interaction coefficients, the present computation results are compared with the published results for a rectangular box and a vertical circular cylinder model floating closely in regular waves, and a satisfactory agreement is observed. Finally, numerical simulations are performed for two identical rectangular barges floating close to each other in the tandem arrangement in regular waves. During the computations, the gap between the floating barges is varied and the occurrence of hydrodynamic resonances in the gap is also examined. Lastly, considering the analysis for the multi-body case, a few conclusions are made.